2020
DOI: 10.1787/0cd3da6b-en
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the 2019 Total Official Support for Sustainable Development (TOSSD) data survey

Abstract: Abbreviations and acronyms Executive summary 1 Introduction 2 Methodology and definitions used in this study 2.1. Objectives of the study 2.2. Methodology 2.2.1. Methodology and definitions used in this study 2.3. Limitations 3 Lessons learnt on the usefulness of TOSSD as a measurement framework for the Sustainable Development Goals (SDG) era 3.1. TOSSD responds to developing countries' needs for information on external financing for sustainable development (pillar I) 3.1.1. TOSSD has the potential to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…For example understanding the determinants of cancer or dementia is essential for developing effective prevention or treatment interventions, and early basic transversal research on unknown pathogens helps prepare for future pandemics. 25 A recent study has demonstrated that all 210 new drugs approved by the US Food and Drug Administration between 2010 and 2016 were associated with published research funded by the NIH and that more than 90% of this research was represented by "basic research related to the biological targets for drug action rather than the drugs themselves" (Galkina Cleary et al, 2018 [21]).…”
Section: The Current Broad Coverage Of Health Randd Topics In Tossd Is Appropriate With a Measurement Approach Focussed On Global Sustainmentioning
confidence: 99%
See 1 more Smart Citation
“…For example understanding the determinants of cancer or dementia is essential for developing effective prevention or treatment interventions, and early basic transversal research on unknown pathogens helps prepare for future pandemics. 25 A recent study has demonstrated that all 210 new drugs approved by the US Food and Drug Administration between 2010 and 2016 were associated with published research funded by the NIH and that more than 90% of this research was represented by "basic research related to the biological targets for drug action rather than the drugs themselves" (Galkina Cleary et al, 2018 [21]).…”
Section: The Current Broad Coverage Of Health Randd Topics In Tossd Is Appropriate With a Measurement Approach Focussed On Global Sustainmentioning
confidence: 99%
“…See the interviews with experts from WHO, UNU-IIGH, Wellcome Trust or the NIH 25. For example the Disease X in WHO's R&D Blueprint is based on the enabling of this early enabling research.…”
mentioning
confidence: 99%